2009
DOI: 10.1074/jbc.m109.060384
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Expression of Collagen IV in Lens Activates Unfolded Protein Response Resulting in Cataract

Abstract: Human diseases caused by mutations in extracellular matrix genes are often associated with an increased risk of cataract and lens capsular rupture. However, the underlying mechanisms of cataract pathogenesis in these conditions are still unknown. Using two different mouse models, we show that the accumulation of collagen chains in the secretory pathway activates the stress signaling pathway termed unfolded protein response (UPR). Transgenic mice expressing ectopic Col4a3 and Col4a4 genes in the lens exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 92 publications
(66 reference statements)
5
94
0
Order By: Relevance
“…If collagen chains accumulate in patient cells, then increased storage of HSP47 can be expected. 24,26 Under standard culture conditions, HSP47 staining was comparable in patient and control cells, suggesting no accumulation of unfolded collagen chains (Supplementary Figure S3). Subsequently, we analysed whether KDEL staining under standard and stress conditions, induced by DTT, would detect ER stress in patient cells.…”
Section: Er Stress Response and Apoptosismentioning
confidence: 96%
See 2 more Smart Citations
“…If collagen chains accumulate in patient cells, then increased storage of HSP47 can be expected. 24,26 Under standard culture conditions, HSP47 staining was comparable in patient and control cells, suggesting no accumulation of unfolded collagen chains (Supplementary Figure S3). Subsequently, we analysed whether KDEL staining under standard and stress conditions, induced by DTT, would detect ER stress in patient cells.…”
Section: Er Stress Response and Apoptosismentioning
confidence: 96%
“…This accumulation activates the unfolded protein response, a well-known ER stress response preceding apoptosis. 20,24,26 As the c.3206delC COL4A2 mutation predicts a null-allele and no such mutations have been described in human COL4A1 patients, we investigated the pathogenic mechanism of this mutation in cultured skin fibroblasts from proband II-2. We wondered whether ER stress could be induced by abnormal stoichiometry of COL4A1 and COL4A2 chains, because of reduced COL4A2 synthesis.…”
Section: Er Stress Response and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical staining for β-crystallin was performed as described previously (Firtina et al, 2009). Immunohistochemical staining for pErk1/2 (Cell Signaling, cs4377s; 1:50) and pAKT (Cell Signaling, cs9271s; 1:50) was performed on antigen-retrieved paraffin sections using the CSAII Biotin-Free Tyramide Signal Amplification Kit with the CSA II Rabbit Link (Dako, Agilent).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In lens fiber cells, expression of either ectopic collagen IV isoforms or mutant collagen IV -chain induces ER stress and impairs fiber cell differentiation, leading to cataract formation (Firtina et al, 2009); cell death is observed only in a group of ectopic collagen-IV-expressing fiber cells that experience prolonged UPR activation. ER-stress-inducing drugs result in dedifferentiation in a differentiated thyroid cell line through a Srcmediated signaling pathway (Ulianich et al, 2008).…”
Section: Journal Of Cell Science 123 (13)mentioning
confidence: 99%